Carcinoembryonic antigen-related cell adhesion molecule (CEACAM)-binding recombinant polypeptide confers protection against infection by respiratory and urogenital pathogens - Hill,DJ; Edwards,AM; Rowe,HA; Virji,M (Mol.Microbiol., 2005)
The human-specific pathogens Neisseria meningitidis, N. gonorrhoea, Haemophilus influenzae and Moraxella catarrhalis share the property of targeting the carcinoembryonic antigen (CEA)-related cell adhesion molecules (CEACAMs) expressed on human epithelia. CEACAMs are signalling receptors implicated in cell adhesion and regulation of several physiological functions. Their targeting by pathogens can lead to tissue invasion. Although the CEACAM-binding ligands of the bacteria are structurally diverse, they target a common site on the receptor. We have generated a recombinant polypeptide that blocks the interactions of the mucosal pathogens with human epithelial cells and antibodies against it inhibit M. catarrhalis interactions with the receptor. As such, it is a potential antimicrobial agent to prevent infection via a strategy unlikely to promote bacterial resistance and a vaccine candidate against M. catarrhalis. In addition, it could serve more widely as a novel research tool and as a potential therapeutic agent in CEACAM-based physiological disorders